2014
DOI: 10.3168/jds.2013-7748
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Minnesota Easy Culture System II Bi-Plate and Tri-Plate for identification of common mastitis pathogens in milk

Abstract: The objective of this study was to validate use of the Minnesota Easy Culture System II Bi-Plate and Tri-Plate (University of Minnesota Laboratory for Udder Health, St. Paul) to identify common mastitis pathogens in milk. A total of 283 quarter and composite milk samples submitted to the University of Minnesota Laboratory for Udder Health during the spring of 2010 were cultured simultaneously using 3 methods: standard laboratory culture (reference method) and the Minnesota Easy Culture System II Bi-Plate and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
62
3
13

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(87 citation statements)
references
References 16 publications
9
62
3
13
Order By: Relevance
“…(Rowbotham and Ruegg, 2016). Although previous research has shown that culture-based systems can only accurately differentiate gram-positive from gram-negative bacteria (Royster et al, 2014), before the study began, veterinarians and managers employed on both farms commonly used OFC to guide mastitis treatment decisions, and at the beginning of the study, they were confident in their ability to differentiate E. coli from Klebsiella spp. Our results indicated that differentiation of E. coli from Klebsiella spp.…”
Section: Discussionmentioning
confidence: 99%
“…(Rowbotham and Ruegg, 2016). Although previous research has shown that culture-based systems can only accurately differentiate gram-positive from gram-negative bacteria (Royster et al, 2014), before the study began, veterinarians and managers employed on both farms commonly used OFC to guide mastitis treatment decisions, and at the beginning of the study, they were confident in their ability to differentiate E. coli from Klebsiella spp. Our results indicated that differentiation of E. coli from Klebsiella spp.…”
Section: Discussionmentioning
confidence: 99%
“…and Streptococcus sp. and evaluation of Staphylococcus aureus presence in milk [ 12 ]. Nevertheless, using these other techniques the assessment of colony appearance is required for detailed identification of milk pathogens and may reduce the predictive value of on-farm culture systems when conducted by farm personnel.…”
Section: Introductionmentioning
confidence: 99%
“…Although several laboratory tools for microbiological diagnosis of IMI for dairy farmers and their veterinarians are available currently, these are rarely used to support treatment decisions (Owens et al, 1997;Lago et al, 2011a). The small number of milk samples submitted to bacteriological laboratories can be explained by the related costs, by the required effort of the farmer involved (Royster et al, 2014), and by the time-to-result (Neeser et al, 2006;Lago et al, 2011a). The current laboratory microbiological diagnostic methods are not considered suitable to base targeted treatment of CM in practice on, because of a time lag of >24 h between sampling and result (Viora et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the delay due to the long time-to-result, the use of onfarm mastitis diagnostics has expanded in countries such as the United States and Canada (Roberson, 2003;Cameron et al, 2013). With on-farm mastitis diagnostics, different categories of mastitis pathogens may be identified (Viora et al, 2014), leading to faster treatment decisions (Lago et al, 2011a,b;Royster et al, 2014) and selective use of antimicrobial agents in CM (Pinzón-Sánchez et al, 2011). In many countries in Europe, however, it is still common practice to treat all cases of CM with antimicrobial agents (Viora et al, 2014), which may be due to the lack of microbiological mastitis diagnostic tests considered suitable by farmers for making treatment decisions.…”
Section: Introductionmentioning
confidence: 99%